E-k Relation of Valence Band in Arbitrary Orientation/Typical Plane Uniaxially Strained - Zhang Chao; Xu Da-Qing; Liu Shu-Lin; Liu Ning-Zhuang (Advances in Condensed Matter Physics)
Uniaxial strain technology is an effective way to improve the performance of the small size CMOS devices, by which carrier mobility can be enhanced. The E-k relation of the valence band in uniaxially strained Si is the theoretical basis for understanding and enhancing hole mobility. The solving procedure of the relation and its analytic expression were still lacking, and the compressive results of the valence band parameters in uniaxially strained Si were not found in the references. So, the E-k relation has been derived by taking strained Hamiltonian perturbation into account. And then the valence band parameters were obtained, including the energy levels at Γ point, the splitting energy, and hole effective masses. Our analytic models and quantized results will provide significant theoretical references for the understanding of the strained materials physics and its design.